Control interno y su incidencia en la gestión administrativa del patronato municipal del cantón La Maná, año 2013 - Chávez Coro, Cinthia Johanna (2015)
This research was conducted at the Municipal Cantón La Maná, to determine the incidence of internal control in administrative management in the period 2013 to several factors it as the fulfillment of the legal basis is analyzed, specifically the Organic Code of Territorial Organization Autonomy and Decentralization COOTAD, for which an interview was applied to the president of the institution.. In the process of this research indicators were also applied to measure the level of effectiveness of the management of the entity providing efficiency and effectiveness parameters to fit the changing environment of organizations. This process arises from field research and literature, vital to acquire information, which is then used for planning, implementation and issue a report of internal control. In this paper the observation was also used to know preliminarily the control environment in which they develop the activities of the institution, infrastructure and different departments. the evaluation of internal control results in the components of risk assessment and monitoring risk have a higher percentage with 25.71% and 19.17% respectively, with respect to the management indicators gives 61,3% confidence which is moderate. Finally it can be concluded that the entity does not have legal counsel which does not allow you to be fully updated with the legal base.